Beyond Bullying: Unpacking The Psychological Toll of Peer Victimization in Higher Education - Moh Fakhri; Muhammad Mugni Assapari (Journal of Educational, Health and Community Psychology, 2026)
Peer victimization remains a prevalent yet underexamined phenomenon in higher education, particularly within Indonesian Islamic university contexts. This quantitative cross-sectional study investigated the psychological impact of peer victimization on 341 undergraduate students at Universitas Islam Negeri (UIN) Mataram, focusing on depression, anxiety, and stress as measured by the Depression Anxiety Stress Scales-21 (DASS-21) and the adapted Mynard and Joseph Peer Victimization Scale. Results demonstrated that peer victimization was a statistically significant positive predictor of all three psychological outcomes: depression (β = .542, R² = .294, p < .001), anxiety (β = .497, R² = .247, p < .001), and stress (β = .461, R² = .213, p < .001). Pearson correlation analyses confirmed moderate-to-large effect sizes across all associations (r = .461–.542, all p < .01). The mean peer victimization score (M = 21.38, SD = 6.94) indicated moderate exposure, with 57.5% of respondents endorsing at least moderate victimization. These findings extend existing theoretical frameworks by contextualizing cumulative trauma theory within a socio-religiously stratified Islamic higher education environment, revealing that hierarchical social dynamics and cultural silence amplify the psychological burden of non-physical peer aggression. The study offers empirical groundwork for institution-specific mental health interventions aligned with the socio-cultural values of Indonesian PTKIN institutions.